Creatividad y su influencia en el proceso enseñanza aprendizaje a los estudiantes de la unidad educativa “san juan” parroquia san juan, cantón puebloviejo, provincia los Ríos - Ube Troya, Alba Maira (2016)
In the educational unit San Juan the creativity is a capacity that one has not come developing in the children and girls, in general the alone creativity works her in the first educational years, leaving this way forgotten its importance for the development of the process teaching learning, the students of years means no longer possess a didactics of motivational and creative class, this impacts negatively in its acting, because they meet with a great contrast comparing with their inferior years. This makes the students to get bored in class with easiness, diminish their attention, and bias for the learning, without having the lack of educational interest of the same one, this situation has captured the author of this final report of investigation which has sought by means of its investigatory work to give with a possible solution that consents the development of the creativity in the students of the fifth year of basic education of the educational unit San Juan